Laparoscopic versus open liver resection for colorectal liver metastasis: an umbrella review - Pinto, Federico; Pangrazio, Marco Di; Martinino, Alessandro; Todeschini, Letizia; Toti, Francesco; Cristin, Luca; Caimano, Miriam; Mattia, Amelia; Bianco, Giuseppe; Spoletini, Gabriele; Giovinazzo, Francesco (Frontiers in Oncology, 2024)
Introduction This study comprehensively compared laparoscopic liver resection (LLR) to open liver resection (OLR) in treating colorectal cancer liver metastasis (CRLM). Methods A systematic review of relevant literature was conducted to assess a range of crucial surgical and oncological outcomes. Results Findings indicate that minimally invasive surgery (MIS) did not significantly prolong the duration of surgery compared to open liver resection and notably demonstrated lower blood transfusion rates and reduced intraoperative blood loss. While some studies favored MIS for its lower complication rates, others did not establish a statistically significant difference. One study identified a lower post-operative mortality rate in the MIS group. Furthermore, MIS consistently correlated with shorter hospital stays, indicative of expedited post-operative recovery. Concerning oncological outcomes, while certain meta-analyses reported a lower rate of cancer recurrence in the MIS group, others found no significant disparity. Overall survival and disease-free survival remained comparable between the MIS and open liver resection groups. Conclusion The analysis emphasizes the potential advantages of LLR in terms of surgical outcomes and aligns with existing literature findings in this field. Systematic review registration [website], identifier [registration number].